Ash seedlings in a reciprocal transplant experiment—the extent of damage of mature forest stands affects ash offspring performance - Haupt, Katharina S.; Mausolf, Katharina; Lassen, Jane; Music, Pia; Schippmann, Marei; Schrautzer, Joachim; Erfmeier, Alexandra (Frontiers in Forests and Global Change, 2024)
In past decades, ash dieback has caused a rapid decline of European ash (Fraxinus excelsior) in temperate forests of Europe. Numerous studies focus on mitigating the negative impacts of ash dieback to forest ecosystems or identifying resistant genotypes. The role of natural selection toward genotypes withstanding ash dieback for ash regeneration has been less frequently studied with experimental means to date. This is, however, necessary in times of global change, because the preservation of ash in Europe’s forests will depend, above all, on the adaptability of the future generations of ash trees. To quantify the extent and effects of ash dieback severity for ash regeneration we selected five forest stands moderately damaged and five forest stands highly damaged by ash dieback, in Schleswig-Holstein, Germany. We reciprocally transplanted naturally regenerated ash seedlings sampled in the field between these 10 sites. A shading treatment added to each half of the plots per site was meant to test for effects of altered light conditions in the herb layer due to canopy opening caused by ash dieback. With this approach, we tested seedling survival, performance and fungal infection for an interacting effect of origin and target site in regard to ash dieback severity and environmental factors over 2 years and recorded leaf traits (specific leaf area, leaf dry matter content) in the second year. Reduced light conditions under the shading nets had strong effects, influencing first year performance and infection probability as well as second year survival, growth and leaf trait characteristics. Soil conditions had only a marginal influence on transplanted seedlings. Transplantation direction between moderately and highly damaged sites affected infection marginally during the first year and survival as well as leaf traits significantly during the second year. Most notably, seedlings transplanted from moderately damaged to severely damaged sites exhibited the highest infection probability and lowest SLA, while seedlings transplanted vice versa were least likely to be infected and exhibited the highest SLA. Results hint at a first filtering effect by the ash dieback history of a forest stand and might indicate a transition from ecologically to evolutionary driven differentiation of ash seedling responses.